Reliable Long-Range and High Ambient Noise Underwater Communication - Andronis, Nicholas (Curtin University, 2019)
Long-Range and high ambient noise underwater communication reliability improvement via sea trail performance validation of whole-of-system algorithm and engineering optimisations. The resulting 10 dB performance improvement can be used to increase the transmit source level by up to 10 dB, extend communication range by 50%, operate in environments with up to 10 dB louder ambient noise, reduce hydro-acoustic noise pollution or lowering battery power consumption with the potential of ocean powered networked communication.